Metabolic exploration of glycogen accumulating organisms’ sludge with Candidatus Contendobacter in enhanced biological phosphorus removal - Shang Wang; Yuchao Liu; Yujie Cai; Xuan Wang; Bin Xue; Sheng Li; Yiqiu Fang; Chao Li; Jingfeng Wang (Journal of Environmental Sciences, 2026)

Multidrug-resistant plasmid modulates ammonia oxidation efficiency in Nitrosomonas europaea through cyclic di-guanylate and acyl-homoserine lactones pathways - Jinrui Cao; Chen Zhao; Lin Bo; Xinxin He; Yuchao Liu; Shang Wang; Bin Xue; Jingfeng Wang (Bioresource Technology, 2026)

Explore the relationship between Bowen ratio and evapotranspiration in wetlands using the maximum entropy production model - Huaiwei Sun; Leying Fu; Weiguang Wang; Jie Xue; Jing Wang; Weihong Liao; Haicheng Li; Xunlai Sun; Yong Yang; Jingfeng Wang; Hong Zhang; Fulong Chen; et al. (Journal of Hydrology, 2025)

No widespread decline in canopy conductance under elevated atmospheric CO2 - Guoqiang Wang; Baolin Xue; Jürgen Knauer; David Helman; Shengli Tao; Yiqi Luo; Junping Wang; Yinglan A; Yuntao Wang; Hua’an Jin; Qingqing Fang; Qiao Wang; et al. (Agricultural and Forest Meteorology, 2025)

Relic DNA obscures bacterial diversity and interactions in ballast tank sediment - Zhaozhao Xue; Haoze He; Yangchun Han; Wen Tian; Shengjie Li; Jingfeng Guo; Pei Yu; Lina Qiao; Wei Zhang (Environmental Research, 2025)

Environmental RNA metabarcoding for ballast water microbial diversity: Minimizing false positives - Zhaozhao Xue; Wen Tian; Yangchun Han; Shengjie Li; Jingfeng Guo; Haoze He; Pei Yu; Wei Zhang (Science of The Total Environment, 2024)

A High-Precision, Ultra-Short Baseline Positioning Method for Full Sea Depth - Yeyao Liu; Jingfeng Xue; Wei Wang (Journal of Marine Science and Engineering, 2024)
To fulfill the demand for high-precision underwater acoustic positioning at full sea depth, an ultra-short baseline (USBL) positioning method with the square array based on the least squares estimating signal parameters via rotational invariance techniques (LS-ESPRIT) algorithm is presented in this paper. A combination of beam tracking and beamforming is employed to improve the accuracy of direction-of-arrival (DOA) estimation and, consequently, enhance overall positioning accuracy. In order to mitigate the issue of position jumping resulting from phase ambiguity in traditional four-element cross arrays, we have improved the stability of the positioning algorithm by utilizing a multi-element square array and employing the LS-ESPRIT algorithm for DOA estimation. Furthermore, the signal detection method integrating the correlation coefficient and ascending/descending chirp signals is employed to enhance the reliability of the location algorithm. Simulation analysis and experimental results demonstrate that the proposed algorithm effectively enhances positioning accuracy and improves the problem of jumping in positioning results.

An automatic tracking method for fruit abscission of litchi using convolutional networks - Tong Huang; Jingfeng Guo; Long Yu; Houbin Chen; Zuanxian Su; Yueju Xue (Computers and Electronics in Agriculture, 2024)

Sea cucumber intestinal osteotropic peptide promotes tibial fracture healing in osteoporotic mice by promoting glutamine metabolism - Haowen Yin; Sun Jin Hur; Tianqi Zhang; Hongying Liu; Hao Yue; Jingfeng Wang; Hongwei Zheng; Changhu Xue (Food Bioscience, 2024)

A cell-free fluorescence biosensor based on allosteric transcription factor NalC for detection of pentachlorophenol - Shuting Chen; Chen Zhao; Xiaodan Kang; Xi Zhang; Bin Xue; Chenyu Li; Shang Wang; Xiaobo Yang; Chao Li; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Biotechnology Letters, 2024)

Chlorite and bromate alter the conjugative transfer of antibiotic resistance genes: Co-regulation of oxidative stress and energy supply - Jinrui Cao; Bin Xue; Shuran Yang; Xiaobo Yang; Xi Zhang; Zhigang Qiu; Zhiqiang Shen; Jingfeng Wang (Journal of Hazardous Materials, 2024)

Significantly enhanced biodegradation of profenofos by Cupriavidus nantongensis X1T mediated by walnut shell biochar - Genrong Zhang; Jingfeng Xue; Yufei Zhang; Jia Ye; Nan Zhang; Liancheng Fang; Taozhong Shi; Xin Ma; Hui Li; Rimao Hua (Journal of Hazardous Materials, 2024)

Multidrug-resistant plasmid RP4 inhibits the nitrogen removal capacity of ammonia-oxidizing archaea, ammonia-oxidizing bacteria, and comammox in activated sludge - Zhaohui Zhang; Lin Bo; Shang Wang; Chenyu Li; Xi Zhang; Bin Xue; Xiaobo Yang; Xinxin He; Zhiqiang Shen; Zhigang Qiu; Chen Zhao; Jingfeng Wang (Environmental Research, 2024)

The occurrence, ecological risk, and control of disinfection by-products from intensified wastewater disinfection during the COVID-19 pandemic - Bin Xue; Xuan Guo; Jinrui Cao; Shuran Yang; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Science of The Total Environment, 2023)

Transcriptomic analysis of the hepatopancreas of white shrimp Penaeus vannamei following experimental infection with the Vibrio parahaemolyticus TJA114 - Xue Zhang; Zhuoran Han; Feng Chen; Xueliang Sun; Jingfeng Sun (Aquaculture, 2023)

Multidrug-resistant plasmid RP4 increases NO and N2O yields via the electron transport system in Nitrosomonas europaea ammonia oxidation - Jia Li; Chen Zhao; Chenyu Li; Bin Xue; Shang Wang; Xi Zhang; Xiaobo Yang; Zhiqiang Shen; Lin Bo; Xinxin He; Zhigang Qiu; Jingfeng Wang (Water Research, 2023)

Counting piglet suckling events using deep learning-based action density estimation - Haiming Gan; Jingfeng Guo; Kai Liu; Xinru Deng; Hui Zhou; Dehuan Luo; Shiyun Chen; Tomas Norton; Yueju Xue (Computers and Electronics in Agriculture, 2023)

Revisiting the role of transpiration in the variation of ecosystem water use efficiency in China - Huaiwei Sun; Mengge Lu; Yong Yang; Jianing Chen; Jingfeng Wang; Dong Yan; Jie Xue; Wenxin Zhang (Agricultural and Forest Meteorology, 2023)

Docosahexaenoic acid inhibits pheromone-responsive-plasmid-mediated conjugative transfer of antibiotic resistance genes in Enterococcus faecalis - Hongrui Zhou; Xiaobo Yang; Yutong Yang; Yuanyuan Niu; Jing Li; Xinyue Fu; Shang Wang; Bin Xue; Chenyu Li; Chen Zhao; Xi Zhang; Zhiqiang Shen; et al. (Journal of Hazardous Materials, 2023)

Recent advance in the investigation of aquatic “blue foods” at a molecular level: A proteomics strategy - Yanchao Wang; Yaoguang Chang; Hu Hou; Jingfeng Wang; Changhu Xue (Trends in Food Science & Technology, 2023)

Monitoring and evaluation of antibiotic resistance genes in three rivers in northeast China - Chen Zhao; Chenyu Li; Xiaoming Wang; Zhuosong Cao; Chao Gao; Sicong Su; Bin Xue; Shang Wang; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Environmental Science and Pollution Research, 2022)

Characterization of a novel Vibrio parahaemolyticus host-phage pair and antibacterial effect against the host - Chao Gao; Xiaobo Yang; Chen Zhao; Chenyu Li; Shang Wang; Xi Zhang; Bin Xue; Zhuosong Cao; Hongrui Zhou; Yutong Yang; Zhiqiang Shen; Pingfeng Yu; et al. (Archives of Virology, 2022)

Study on the effects of the different polar group of EPA-enriched phospholipids on the proliferation and apoptosis in 95D cells - Yao Guo; Qin Zhao; Yingying Tian; Yuanyuan Liu; Ziyi Yan; Changhu Xue; Jingfeng Wang (Marine Life Science & Technology, 2021)
EPA-enriched phosphatidylcholine (EPA-PC) and EPA-enriched phosphatidylethanolamine (EPA-PE) are newly identified marine phospholipids. The polar group of phospholipids is known to influence EPA-phospholipid activity. However, the differences in anti-tumor effects between EPA-PC and EPA-PE have not been reported. In this study, we evaluated the effects of two forms of EPA on the proliferation and apoptosis in the lung-cancer cell line 95D as well as possible molecular mechanisms. Our results showed that EPA-PC effectively inhibited proliferative activity and promoted apoptosis of 95D cells in a dose-dependent manner, while EPA-PE had no effect on cell proliferation, although it slightly promoted apoptosis. Western blot results showed that EPA-PC and EPA-PE upregulated the expression of PPARγ, RXRα, and PTEN, and downregulated the PI3K/AKT signaling pathway. Furthermore, EPA-PC and EPA-PE induced the expression of the pro-apoptotic gene, Bax, and reduced the expression of the anti-apoptotic gene, Bcl-xl. Additionally, EPA-PC and EPA-PE promoted the release of cytochrome c and activated the apoptotic enzyme-cleaved caspase-3. These data suggest that the anti-tumor effect of EPA-phospholipids may be exerted via a PPARγ-related mechanism. EPA-PC was more efficacious as compared to EPA-PE, which might be due to the different polar groups of phospholipids.

Sialoglycoproteins Isolated from the Eggs of Gadus morhua Inhibit Bone Resorption in Ovariectomized Rats by Suppressing the MAPK and NF-κB Pathways - Lei Mao; Yiming Wang; Meiling Wang; Yufeng Dai; Jingfeng Wang; Changhu Xue (Journal of Ocean University of China, 2019)

Sialoglycoprotein isolated from Carassius auratus eggs promotes osteogenesis by stimulating mesenchymal stem cells to commit to osteoblast differentiation - Lei Mao; Meiling Wang; Xingjun Xi; Yufeng Dai; Na Wang; Jingfeng Wang; Changhu Xue (Cell and Tissue Research, 2019)

Preparation, Gel Electrophoresis Analysis, and Nutritional Evaluation of a Functional Krill Protein Concentrate with Low Fluoride Level from Antarctic krill ( Euphausia superba ) - Li’ang Yin; Xiaoming Jiang; Yan Fan; Jingfeng Wang; Changhu Xue; Yong Xue (Journal of Aquatic Food Product Technology, 2017)

Enrichment, Distribution of Vanadium-Containing Protein in Vanadium-Enriched Sea Cucumber Apostichopus japonicus and the Ameliorative Effect on Insulin Resistance - Yanjun Liu; Qingxin Zhou; Yanlei Zhao; Yiming Wang; Yuming Wang; Jingfeng Wang; Jie Xu; Changhu Xue (Biological Trace Element Research, 2016)

Assessment of total and organic vanadium levels and their bioaccumulation in edible sea cucumbers: tissues distribution, inter-species-specific, locational differences and seasonal variations - Yanjun Liu; Qingxin Zhou; Jie Xu; Yong Xue; Xiaofang Liu; Jingfeng Wang; Changhu Xue (Environmental Geochemistry and Health, 2016)

Green Synthesis of Oxovanadium(IV)/chitosan Nanocomposites and Its Ameliorative Effect on Hyperglycemia, Insulin Resistance, and Oxidative Stress - Yanjun Liu; Xu Jie; Yongli Guo; Xin Zhang; Jingfeng Wang; Changhu Xue (Biological Trace Element Research, 2016)

Preparation of Triacylglycerols Enriched in DHA from Single Cell Glycerides via Molecular Distillation and Enzymatic Glycerolysis - Zhaomin Sun; Lu Yang; Changhu Xue; Zhengxia Guo; Haihua Cong; Yuming Wang; Yong Xue; Jingfeng Wang (Journal of Aquatic Food Product Technology, 2015)

Effects of dietary sea cucumber saponin on the gene expression rhythm involved in circadian clock and lipid metabolism in mice during nighttime-feeding - Min Wen; Jie Cui; Jie Xu; Yong Xue; Jingfeng Wang; Changhu Xue; Yuming Wang (Journal of Physiology and Biochemistry, 2014)

Hpyerglycemic effect of a mixture of sea cucumber and cordyceps sinensis in streptozotocin-induced diabetic rat - Shiwei Hu; Jingfeng Wang; Zhaojie Li; Jia Fu; Yuming Wang; Changhu Xue (Journal of Ocean University of China, 2014)

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

Antioxidation activities of low-molecular-weight gelatin hydrolysate isolated from the sea cucumber Stichopus japonicus - Jingfeng Wang; Yuming Wang; Qingjuan Tang; Yi Wang; Yaoguang Chang; Qin Zhao; Changhu Xue (Journal of Ocean University of China, 2010)